Woman Leadership Reflected In Phyllida Lloyd's The Iron Lady Movie (2011): A Feminist Approach - Astuti, Desi Antri; , Dr. Phil. Dewi Candraningrum, S.Pd, M. Ed; , Drs. H. Abdillah Nugroho, M. Hum (2013)
The major problem of this study is how woman leadership are reflected in Phyllida lloyd's The Iron lady movie (2011). The study is aimed to analyze the movie based on structural elements and to analyze the movie based on the feminist approach. The object of this study is The Iron Lady movie by Phyllida Lloyd. This study belongs to descriptive qualitative research. There are two types of data source. First, the primary data is The Iron Lady movie that was released in 2011 and the secondary data are books or any information relation to the practice of woman leadership that support the feminist approach. Both data are collected through library research and analyzed by descriptive analysis. Based on the analysis, the researcher draws the following conclusions. First, based on the structural analysis of each element, it shows that the character and characterization, casting plot, setting, point of view, theme, mise-en-scene, cinematography, sound, and editing are related to each other. Second, based on the feminist analysis, the woman's position, woman's role, woman's right, and woman's participation are reflected in Margaret Thatcher's life. All of them involved in the process of Margaret Thatcher becoming a leader. Third, Margaret Thatcher fulfills the characteristic of woman leadership that can be considered as transformational leader.